Supracondylar fractures in children: management and treatment - Micheloni, Gian Mario; Novi, Michele; Leigheb, Massimiliano; Giorgini, Andrea; Porcellini, Giuseppe; Tarallo, Luigi (Acta Biomedica Atenei Parmensis, 2021)
Supracondylar humeral fractures are widely considered the most common elbow fracture in children. Gartland classification plays a fundamental role in decision-making regarding management and prognosis. Recent literature recommends conservative management for non or minimally displaced fractures, whereas there seems to be a trend towards surgical treatment for all displaced fractures. The preferred treatment for displaced Gartland II and Gartland III fractures is closed reduction and percutaneous fixation with lateral pins. In particular patterns medial pin is recommended for obtain a stable construct. Neurovascular complications are mostly associated with Type III fractures and sometimes surgical exploration with fracture reduction is needed. Correct diagnosis and proper management protocol is mandatory for avoid early and late complications such as neurovascular impairment and malunion.